PENGARUH DISKUSI KELOMPOK DALAM PEMBELAJARAN MATEMATIKA TERHADAP SIKAP DAN HASIL BELAJAR SISWA SMP DI KOTA SERANG - Lisa Pradika; Syamsuri Syamsuri (Universitas Sultan Ageng Tirtayasa, 2019)
There are still many students who think that mathematics is difficult, so it takes a method that involves the activeness of students so that can enhance their attitudes and mathematics learning achievement. To overcome this, use the method of discussion is a means of channeling the right to these problems. This study examined a large representative sample of eighth-grade students in the Serang City to knowing the effect of group discussion in mathematics learning towards attitudes and learning achievement. Results showed that students who have group discussions in mathematics learning have a positive effect towards attitudes and learning achievement than students who have never learning using group discussions.